A study on the mechanism and control technology of strong mine pressure in parallel coal pillar and hard roof mining - Zhou, Haifeng; Huang, Qingxiang; He, Yanpeng; Wang, Qingxiong; Wei, Yehao (Frontiers in Earth Science, 2024)
In multi-seam mining, as mining ranges expand and depths increase, the strong ground pressure exerted on the lower coal-seam working faces (WFs) or roadways by coal pillars (CPs) and the hard roof between the interburdens becomes increasingly severe, leading to periodic roof-fall accidents. This study focused on the 42108 WF of the 4–2 coal seam in the Buertai Coal Mine of Shandong mining. It combined field tests, theoretical research, and numerical calculations to investigate the superposition or amplification of ground pressure as WF traversed the CP with the hard roof between interburdens. The ground pressure behavior of WF entering and exiting the CP stage progressed from strong to weak: exiting the CP > under the CP > entering the CP, with the CP stage being prone to a strong ground pressure occurrence. We proposed the influence mechanism of strong ground pressure and a seesaw structural mechanics model under the mining conditions with parallel CPs and hard roofs. The relationship between the geometric structure movement and stress evolution of the seesaw space of the overlying hard roof was analyzed, revealing the mechanism behind stress increase, evident damage, and the likelihood of dynamic disasters within 5–10 m from the CP boundary of the WF. The stress concentration factor (SCF) of the advance abutment pressure in the coal wall was the primary controlling factor determining seesaw instability, effectively ensuring safe and efficient mining practices. This research holds significant theoretical importance and practical engineering value for controlling strong mine pressure under the overlying CPs and hard roofs.